Reduce the grammar to Chomsky normal formS→ ABAC | aCAA→ aA | εB→ bB | εC→ dD→ f
Question
Reduce the grammar to Chomsky normal form
S → ABAC | a
A → aA | ε
B → bB | ε
C → d
D → f
Solution
To reduce the given grammar to Chomsky normal form, we need to follow these steps:
Step 1: Eliminate ε-productions (productions that can derive the empty string ε). In this grammar, we have ε-productions for the variables B and C. To eliminate them, we replace B with ε in all the productions where it appears and remove the ε-production for B. Similarly, we replace C with ε in all the productions where it appears and remove the ε-production for C. After this step, the grammar becomes:
S → ABAC | ABACAA | aA | a | bB | b | dD | f
Step 2: Eliminate unit productions (productions of the form A → B). In this grammar, we have unit productions for the variables S, A, and B. To eliminate them, we replace S with ABAC in the first production, A with aA in the second production, and B with bB in the fifth production. After this step, the grammar becomes:
S → ABAC | ABACAA | aA | a | bB | b | dD | f A → aA | a B → bB | b
Step 3: Eliminate productions with more than two variables on the right-hand side. In this grammar, we have the production S → ABACAA that has more than two variables on the right-hand side. To eliminate it, we introduce a new variable X and rewrite the production as follows:
S → ABACX X → AA
After this step, the grammar becomes:
S → ABACX | aA | a | bB | b | dD | f A → aA | a B → bB | b X → AA
Step 4: Convert all remaining productions to have exactly two variables or terminals on the right-hand side. In this grammar, all the remaining productions already have exactly two variables or terminals on the right-hand side. Therefore, no further modifications are needed.
The final grammar in Chomsky normal form is:
S → ABACX | aA | a | bB | b | dD | f A → aA | a B → bB | b X → AA
Similar Questions
You have a context-free grammar (CFG) defined as follows:S → aSbS → εWhich of the following strings is generated by this CFG?1 point"aabbb""aaabb""ab""bbb"
Use the string “ababab” to show that the following grammar is ambiguous: 𝑆 → 𝑆𝑆 | 𝑇 𝑇 → 𝑎𝑇𝑏 | 𝑎𝑏
For the given Context free grammar reduce the following grammar SaBDh A Bbc | b DdD
Chomsky's linguistic computational theory generated a model for syntactic analysisthrougha. regular grammarb. regular expressionc. regular wordd. none of these
Suppose A → xBz and B → y, then the simplified grammar would be:Select one:a. None of the mentionedb. A → xBz|xyzc. A → xyz d. A → xBz|B|y
Upgrade your grade with Knowee
Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.